Measuring Segregation of the Poor: Evidence from India. (January 2017) - Dhongde, Shatakshee
Highlights: An analytical framework to measure regional segregation of the poor. A generalized poverty segregation curve is proposed for the first time. Distribution of the poor in India since economic reform is assessed. Segregation of the poor increased despite a decline in average poverty rates in India. Design policies that will promote a more even reduction in poverty within states. Summary: Compared to the extensive literature on measurement of poverty, the question of how the poor are distributed regionally has received less attention. This paper fills the gap in the literature by providing a conceptual framework to measure inequality in the distribution of the poor. A poverty segregation curve is used to compare a region's share of the poor population with its share in the overall population. A unique contribution of the paper is formulating a generalized version of the poverty segregation curve. Unlike the segregation curve, the generalized segregation curve also takes average poverty rates into account while ranking distributions. Thus the generalized segregation curve may rank a distribution with substantially lower poverty rates above a distribution with higher poverty rates, when differences between their segregation curves are relatively small. The segregation curves are used to analyze changes in the distribution of the poor in India since the economic reforms in the early 1990s. Poverty rates and shares among all states, territories, and districts in India are estimated using data from the National Sample Survey Organization in 1994, 2004, and 2010. In the decades following the reforms India witnessed high growth rates and declining poverty rates. Despite the reduction in poverty, our analysis is the first to reveal that there was a significant rise in segregation of the poor over time. Some states had disproportionately high share of the poor compared to their share in the total population. Within states, the extent of segregation was lower among some of the poorest states and higher in less poor states. The generalized segregation curves show that the substantial decline in poverty rates since the reforms was not adequate to compensate the rise in segregation of the poor. Increase in segregation was also evident when the poor are identified as those who lacked education, health, and access to basic services. Reducing the segregation of the poor is important if India is to attain regionally balanced economic growth.